Analisis Penggunaan Bahasa Gaul Remaja di RT 02 Simpang Tiga, Kecamatan Sungai Tebelian, Kabupaten Sintang, Provinsi Kalimantan Barat - Indira Zakya Putrie; Ari Wulandari (PT. Alahyan Publisher Sukabumi, 2025)
This study analyzes the phenomenon of slang language use among adolescents in RT 02 Simpang Tiga, Sungai Tebelian District, Sintang Regency. It aims to understand the social dynamics, technological advancements, and identity search reflected in their communication patterns. This descriptive qualitative research employed observation and in-depth interviews with adolescents aged 12-19 years as subjects. The findings reveal that slang serves as a primary communication tool for adolescents in their daily lives, including popular vocabulary such as